Surgical anatomy of the round window—Implications for cochlear implantation. (3rd January 2018) - Luers, J.C.; Hüttenbrink, K.B.; Beutner, D.
Abstract : Background: The round window is an important portal for the application of active hearing aids and cochlear implants. The anatomical and topographical knowledge about the round window region is a prerequisite for successful insertion for a cochlear implant electrode. Objective of review: To sum up current knowledge about the round window anatomy and to give advice to the cochlear implant surgeon for optimal placement of an electrode. Type of review: Systematic Medline search. Search strategy: Search term "round window[Title]" with no date restriction. Only publications in the English Language were included. All abstracts were screened for relevance, that is a focus on surgical anatomy of the round window. The search results were supplemented with hand searching of selected reviews and reference lists from included studies. Evaluation method: Subjective assessment. Results: There is substantial variability in size and shape of the round window. The round window is regarded as the most reliable surgical landmark to safely locate the scala tympani. Factors affecting the optimal trajectory line for atraumatic electrode insertion are anatomy of the round window, the anatomy of the intracochlear hook region and the variable orientation and size of the cochlea's basal turn. Conclusions: The very close relation to the sensitive inner ear structures necessitates a thorough anatomic knowledge and careful insertion technique, especially when implanting patients with residual hearing. In order to avoid electrode migration between the scalae and to achieve protect the modiolus and the basilar membrane, it is recommended to aim for an electrode insertion vector from postero‐superior to antero‐inferior.